Investigation of the influence of bakery enzymes on non-yeasted dough properties during mixing. (January 2018) - Koksel, Filiz; Scanlon, Martin G.
Abstract: Understanding the influence of bakery enzymes on dough properties during the early stages of the breadmaking process can help optimize the design of enzymes for the bakery industry. The objectives of this study were to determine whether bakery enzymes affected dough aeration during mixing and whether outcomes differed according to flour strength. Doughs were prepared from a strong breadmaking flour and a cookie flour to which various bakery enzymes were added. Dough density was measured, and the ultrasonic phase velocity and attenuation coefficient in the resonance frequency region for bubbles in dough were evaluated. Dough properties differed according to the enzyme and a significant interaction between enzyme type and flour strength was observed. For strong breadmaking wheat flour doughs, the greatest changes were observed for glucose oxidase, followed by xylanase and then cellulose. For the weak flour doughs, the largest changes were observed for doughs containing lipase and xylanase, with the effect of glucose oxidase being much less pronounced. The enzyme-dependent changes in acoustic signatures and in dough density demonstrate that some bakery enzymes influence bread crumb structure as early as at the mixing stage. Highlights: Some bakery enzymes alter gas occlusion during mixing. Ultrasonic signatures reveal changes in dough properties due to enzyme action. Significant interactions occur between enzyme type and flour strength. Enzyme effects on components in the dough matrix govern how gas is occluded in dough. Some enzymes affect bread crumb structure as early as the mixing stage.